The determinants of SME capital structure across the lifecycle - Maria Martinez Cillero; Martina Lawless; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2019)
While differences in capital structure between large and small firms have been extensively researched, relatively less empirical evidence is available explaining cross country differences in the capital structure of SMEs over the life cycle. This is an important gap as many of the theoretical predictions on financing requirements and access can be linked to firm age. In this paper, we explore the determinants of SME capital structure across the age distribution of firms using firm-level panel data for 15 European countries. Our key findings demonstrate the existence of a non-linear relationship between age and capital structure that differs markedly across countries. We also find that firm level collateral and liquidity play a role in determining the age-debt relationship. Finally, we find that the age-debt relationship depends on the country level financial structure with more stock market financing reducing firm leverage disproportionately for young firms while foreign bank lending and bank concentration both increase firm leverage across the lifecycle.
Keywords: D22; D25; 330; SMEs; firm lifecycle; firm indebtedness; comparative analysis; panel data